Interventions to improve screening and appropriate referral of patients with cancer for psychosocial distress: systematic review. Issue 1 (5th January 2018) - McCarter, Kristen; Britton, Ben; Baker, Amanda L; Halpin, Sean A; Beck, Alison K; Carter, Gregory; Wratten, Chris; Bauer, Judith; Forbes, Erin; Booth, Debbie; Wolfenden, Luke
Abstract : Objectives: The primary aim of the review was to determine the effectiveness of strategies to improve clinician provision of psychosocial distress screening and referral of patients with cancer. Design: Systematic review. Data sources: Electronic databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PsycINFO and Cumulative Index to Nursing and Allied Health Literature (CINAHL)) were searched until July 2016. Inclusion criteria: Population: adult patients with cancer and clinical staff members. Intervention: any strategy that aimed to improve the rate of routine screening and referral for detected distress of patients with cancer. Comparison: no intervention controls, 'usual' practice or alternative interventions. Outcome: (primary) any measure of provision of screening and/or referral for distress, (secondary) psychosocial distress, unintended adverse effects. Design: trials with or without a temporal comparison group, including randomised and non-randomised trials, and uncontrolled pre–post studies. Data extraction and analysis: Two review authors independently extracted data. Heterogeneity across studies precluded quantitative assessment via meta-analysis and so a narrative synthesis of the results is presented. Results: Five studies met the inclusion criteria. All studies were set in oncology clinics or departments and used multiple implementation strategies. Using the Grades of Recommendation, Assessment, Development and Evaluation, the overall rating of the certainty of the body of evidence reported in this review was assessed as very low. Three studies received a methodological quality rating of weak and two studies received a rating of moderate. Only one of the five studies reported a significant improvement in referrals. Conclusions: The review identified five studies of predominantly poor quality examining the effectiveness of strategies to improve the routine implementation of distress screening and referral for patients with cancer. Future research using robust research designs, including randomised assignment, are needed to identify effective support strategies to maximise the potential for successful implementation of distress screening and referral for patients with cancer. PROSPERO registration number: CRD42015017518 .